Solid-state fermentation of whole sugarcane and paper sludge for first- and second-generation ethanol production - Van Dyk, Janke (Stellenbosch : Stellenbosch University, 2025)
van Dyk, J. 2025. Solid-state fermentation of whole sugarcane and paper sludge for first- and second-generation ethanol production. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/3c69ae21-8b00-4b43-b0de-b26fca40aa75